Confirmatory study of the usefulness of quantum molecular resonance and microdissectomy for the treatment of lumbar radiculopathy in a prospective cohort at 6 months follow-up - Canós-Verdecho Ángeles; Robledo Ruth; Izquierdo Rosa; Bermejo Ara; Gallach Elisa; Abejón David; Argente Pilar; Peraita-Costa Isabel; Morales-Suárez-Varela María (Scandinavian Journal of Pain, 2024)
Low back pain is a common musculoskeletal complaint and while prognosis is usually favorable, some patients experience persistent pain despite conservative treatment and invasive treatment to target the root cause of the pain may be necessary. The aim of this study is to evaluate patient outcomes after treatment of lumbar radiculopathy (LR) with quantum molecular resonance radiofrequency coblation disc decompression and percutaneous microdiscectomy with grasper forceps (QMRG).